Advantages of greenery in hospital environment - a literature review - Kalender Smajlović, Sedina (Sanitarno inženirstvo, 2023)
Background: Incorporating greenery into hospital environment contributes to the sustainable development goals by mitigating health, environmental and economic problems. Despite the increasing interest in plants, gardens and green roofs in general built environments, the benefits of greenery in hospital environment are still under-researched. The aim of this review was to summarize the relevant literature and describe the benefits of greenery in hospital environment. Methods: The PubMed, Springer Link and CINAHL databases were searched to identify relevant studies and articles published between 2012 and 2023. The keywords used were hospitals, greenery, green systems, vegetation, and room plants. The language restriction was that articles were published in English. Results: Following the PRISMA methodology, seven eligible studies were included in the literature review. Evidence shows that the presence of greenery affects patient health outcomes and the well-being of healthcare staff. Moreover, the healing and therapeutic effects greenery in the hospital environment have been identified. Greenery also has a positive psychological effect on healthcare workers and visitors. Humanizing healthcare spaces and connecting them with nature empowers patients, reduces stress and pain, and improves emotional well-being. Conclusion: The biophilic design concept increases occupant connectivity to the natural environment through vegetation at the location, including implemented green building envelope systems (green walls and roofs) and the introduction of indoor plants. It should be incorporated into the established steps of hospital design. In summary, more research is needed, particularly on the potential impact of plants on hospital-acquired infections.
Keywords: bolnišnica; bolnišnično okolje; ekonomija; okolje; ozelenitev; rastline; sobne rastline; vegetacija; zeleni sistemi; zelenje